Book monitoring system with real-time inventory using RFID technology - Barbieto, Paula Angelica V. (Animo Repository, 2008)
Book monitoring in a library set-up is essential not only for library administrators but for students and faculty as well. Library administrators need to close certain sections of their libraries in order to perform inventory. For students and faculty, the task of locating books in shelves is often disregarded. Searching books in the library can be hard when books that are searched are misplaced or missing from their specified shelves. Borrowing and returning functions of students can also be done without the need for library supervision. Radio Frequency Identification (RFID) Technology used in a library set-up provides solutions to these problems. By applying a program that incorporates the RFID reader with high-frequency tags attached in books, the tasks of library personnel, students and faculty in searching, monitoring and supervising books are supported and made easier.